CuPON the Copper alternative to PON 100 Gb DSL networks. - Cioffi, Joseph M. (IEEE Communications magazine)
This article investigates the ultimate bandwidth limits of a copper DSL binder of 200 telephone line connections, finding the ultimate available shared data bandwidth to be 100 Gb/s. A new "Copper-PON" or, more compactly CuPON1 multidropping DSL architecture enables DSL bandwidth sharing and increases data rates through exploitation of all modes of crosstalk, particularly with the use of vectored2 dynamic spectrum management. The inevitable emerging conclusion raises an intriguing question about the broadband access evolution of telecommunications networks: Why deploy currently available or contemplated passive fiber systems when the existing last kilometer of copper can provide broadband gigabits per second to everyone?